Think-Talk-Write Strategy in Biology Learning: Its Impact on Mastery of the Human Digestive System Concept - Dwi Cahya Nirmala; Baharudin Baharudin; Mombo Kurniati (Journal of Academic Biology and Biology Education, 2024)
Purpose of the study: This study aims to determine the effect of the Think-Talk-Write learning strategy on the mastery of the concept of the human digestive system in junior high school students and to determine the activities and responses of students during Biology learning using this strategy. Methodology: This study used a quasi-experimental method with a two-group pretest-posttest design. The research instruments included multiple-choice tests, observation sheets, and student response questionnaires. The sampling techniques used were purposive sampling and random sampling. Data analysis was performed using the Liliefors test, Fisher's exact test, t-test, and N-Gain analysis. Main Findings: The results of the study showed that the Think-Talk-Write learning strategy significantly influenced mastery of the concept of the human digestive system. Students in the experimental class achieved better learning outcomes than those in the control class. Student activity during learning increased at each meeting, and most students responded positively to the implementation of the Think-Talk-Write strategy in Biology learning. Novelty/Originality of this study: The novelty of this research lies in the specific application of the Think-Talk-Write strategy to the human digestive system to measure junior high school students' conceptual mastery. This study also integrates analysis of conceptual mastery, learning activities, and student responses, providing a more comprehensive picture of the effectiveness of the Think-Talk-Write strategy in biology learning.